Electrochemically-induced TiO2 incorporation for enhancing corrosion and tribocorrosion resistance of PEO coating on 7075 Al alloy. (October 2018) - Akbari, Ehsan; Di Franco, Francesco; Ceraolo, Paolo; Raeissi, Keyvan; Santamaria, Monica; Hakimizad, Amin
Highlights: Bipolar waveform with wider cathodic pulses (W3) prevented the pancakes formation. Titanium oxalate develops TiO2 in anatase and rutile polymorphs in the PEO coating. Coatings with no large pores at the metal/coating interface was created by the W3. The W3 coating showed the best passivation behavior and corrosion performance. The lowest volume loss was also achieved for the W3 coating in tribocorrosion test. Abstract: 7075 Al alloy was PEO-treated in a silicate based electrolyte containing 3 g l -1 potassium titanyl oxalate using unipolar and bipolar pulsed current waveforms. The coating formed by the bipolar waveform with the wider cathodic pulses showed volcano-like surface morphology with no evidence of large pores at the metal/coating interface. It revealed the highest corrosion performance due to the synergistic effect of TiO2 incorporation and structural/morphological features along with a better passivation behavior indicating no pitting susceptibility. For this coating, the tribocorrosion tests showed no potential drop during sliding under 1 N with the lowest volume loss of 0.022 mm 3 .